2019
DOI: 10.24018/ejbmr.2019.4.4.72
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Lifestyle on Purchasing Decision for Samsung Smartphone Products in Jakarta

Abstract: This study is part of a thesis that discussed the factors that affect purchasing decision for Samsung smartphone products in Jakarta and the purpose of this study was to analyze in detail the influence of lifestyle on purchasing decision for Samsung brand smartphone products in Jakarta. This study used primary data in the form of the manual questionnaire and distributed randomly in various regions in Jakarta. The method used was judgment sampling which means the respondent was given questions that had been det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…This research is also in line with research conducted by (Handayani & Kurnianingsih, 2021) where in the study it is said that lifestyle variables have a significant influence on smartphone purchase decisions and product design variables also affect purchase decisions. In addition, the results of this research are also in line with the research conducted (Andi & Ali, 2019) and (Clyde, Hanifah, & Muchlish, 2022).…”
Section: Introductionsupporting
confidence: 87%
“…This research is also in line with research conducted by (Handayani & Kurnianingsih, 2021) where in the study it is said that lifestyle variables have a significant influence on smartphone purchase decisions and product design variables also affect purchase decisions. In addition, the results of this research are also in line with the research conducted (Andi & Ali, 2019) and (Clyde, Hanifah, & Muchlish, 2022).…”
Section: Introductionsupporting
confidence: 87%
“…Halim and Dinaroe (2019) show that lifestyle, money attitude, and personal value significantly affect the purchase decision of Apple products. Andi and Ali (2019) also show that lifestyle positively and significantly affects purchasing decisions for Samsung smartphones in Jakarta.…”
Section: Introductionmentioning
confidence: 83%
“…This research is in line with the previous ones conducted by Wijonarko (2016) that reinforced the conclusion that lifestyle had a dependency on the purchase of gadget because the use of gadget in students got fulfillment to be seen as a broadminded and highly intellectual individuals, by Sutji and Saptomo (2017) that found that lifestyle had a positive and significant dependency on gadget purchases, by Das and Panigrahi (2017) that showed influence on lifestyle was high on the purchasing decisions, by Halim and Dinaroe (2019) that showed lifestyle, money attitude, and personal value affects significantly towards the purchase decision of Apple products, by Andi and Ali (2019) that also showed lifestyle has a positive and significant effect on purchasing decision of Samsung smartphone in Jakarta, by Hidayat (2022) that suggested social media and peer group interaction influence the gadgets impulsive buying, and by Moreover, Oe et al (2022) that suggested Chinese consumers are more concerned with fashionableness in smartphone purchase.…”
Section: Discussionmentioning
confidence: 99%
“…Salah satu sumber biaya itu bermula dari pajak (Ardi, 2016). Mardiasmo (2019) menyampaikan, pembayaran pajak itu sendiri ialah salah satu bentuk kewajiban kenegaraan serta peran Wajib Pajak ketika melaksanakan kewajiban perpajakannya guna anggaran Negara serta pembangunan nasional. Perpajakan sendiri merupakan sumber paling berpengaruh dari pemasukan negara yang menempati persentase paling tinggi di Anggaran Pendapatan dan Belanja Negara (APBN) jika dibandingkan dengan pendapatan lainnya.…”
Section: Pendahuluanunclassified